IMPLEMENTASI PERBAIKAN KUALITAS UNTUK MENURUNKAN PRESENTASE PRODUK REJECT IMPACT TEST PIPA DI PT. WAHANA DUTA JAYA RUCIKA : METODE Plan Do Check Action (KAIZEN) - Kurnia, Angga Muhammad; Imaroh, Tukhas Shilul (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
During 2017 at PT Wahana Duta Jaya Rucika the quality of products calculated by rejecting the Cibitung Plant PVC pipe reached 3.01%, it was above the target set by management at 3%. The highest reject occurred in July 2017, as many as 4.05%, which was dominated by reject, failed line 5 impact test, based on the monitoring data for one year until July 2018, this factor rejected an average of 3.4%. Therefore the researcher wants to know the factors that cause the reject product to fail the impact test and the implementation of quality improvement to reduce the number of reject impact test products by applying the Kaizen (PDCA) method. The type of research used is quantitative research. As well as the design of this study is descriptive exploratory through the kaizen method (eight steps) with 4M + 1E, 5W + 1H, fishbone diagram, RCFA to find the root of existing problems and full factorial DOE to determine process optimization. The results of the study resulted in a failed impact test, namely the absence of a back pressure indicator in the extruder to find out the melt pressure and the optimization of the parameter process in the extruder because so far only using trial and error repair methods, and temperature melt factors, back. The result is a decrease from 3.4% to 0% reject impact test in October to November 2018.